Ditch the NPT. Issue 4 (4th July 2021) - Pretorius, Joelien; Sauer, Tom
Abstract : Without the Nuclear Non-Proliferation Treaty, nuclear-armed states and their allies could no longer rely on their skewed interpretation of it to legitimise continued possession of nuclear weapons.